Hairstylists - Rathburn, Betsy (Minneapolis, MN : Bellwether Media, 2020)
Developed by literacy experts for students in kindergarten through grade three, this book introduces hairstylists to young readers through leveled text and related photos.
A new look -- What are hairstylists? -- What do hairstylists do? -- What makes a good hairstylist?
Includes bibliographical references (page 23) and index.
2.2
K-3
400L
J
Keywords: Hairdressing -- Juvenile literature; Barbers -- Juvenile literature; Hairdressing; Barbers; Readers (Elementary)